Active Labour Market Programmes in Poland Between 2005 and 2010 - Kwiatkowska, Walentyna (Comparative Economic Research. Central and Eastern Europe, 2013)
High unemployment in Poland is a major socio-economic problem. The unemployment rate in Poland reached the level of 16.7% in 2005, 9.3% in 2010 and 9.7% in 2011. Unemployment in Poland is mainly structural, which is reflected in the structural imbalances between labour demand and labour supply with respect to vocational qualifications, professions, and spatial deployment. The main factor determining unemployment is the necessity for structural changes in the Polish economy caused by its transformation and integration with the European Union, changes aimed at enhancement of economic innovation, competitiveness and effectiveness. An active labour market policy plays an important role in a situation characterized by high structural unemployment. Efficiently applied instruments of an active labour market policy can reduce this unemployment. Therefore, the main aim of this paper is to evaluate the role of the active labour market policy in Poland between 2005-2010, taking into consideration the characteristics of its main instruments, its participants, and expenditures.